The Effect of Preliminary Return of Excess Value Added Tax on Value Added Tax Revenue: (Case Study of KPP Pratama Boyolali) - Tjandra, Ronowati; Fajri, Ul'Ulya Zuhrufi; Muid, Dul; Astuti, Ratna Puji (Politeknik Negeri Batam, 2023)
This study aims to determine the suitability of the process flow of filing a preliminary tax return at KPP Pratama Boyolali under current regulations and provide evidence of the effect of preliminary tax returns on the annual tax revenue of KPP Pratama Boyolali. This research is a mixed method research. The data collected are data derived from interviews and document studies. This research uses analysis techniques in the form of interactive model and simple regression analysis using SPSS statistical tools. The results showed that the preliminary refunding process of Value Added Tax in KPP Pratama Boyolali was according to the existing regulations and the variable preliminary refunding of Value Added Tax had no significant effect on Value Added Tax revenue.